Environmental Quality and Management - Franzese, Pier Paolo; Maisto, Giulia; Marco, Anna De; Arena, Carmen; Buonocore, Elvira (Journal of Environmental Accounting and Management, 2026)
This volume gathers theoretical, methodological, and applied papers exploring different issues related to environmental quality and management. Human economy depends on healthy ecosystems capable of ensuring a life support system delivering ecosystem services vital for human well-being. Integrated environmental assessment and environmental accounting are essential research areas to assess the quality of environmental matrices while supporting managers and policy makers with scientifically sound information.